DETERMINANT FACTORS RELATED TO THE INCIDENCE OF ANEMIA IN POST-PART MOTHERS IN THE WORK AREA OF DARUSSALAM COMMUNITY HEALTH CENTER, BANDA ACEH CITY - Rahmisyah Rahmisyah; Nelva Riza; Fitria Fitria (Getsempena Health Science Journal, 2024)
Anemia is a condition in which the blood contains low hemoglobin levels. Hemoglobin is an iron-rich protein that carries oxygen from the lungs to the rest of the body.Anemia in the postpartum period is a condition of postpartum mothers with hemoglobin (Hb) levels < 11 g/dl. As a result, it can interfere with the blood's capacity to transport oxygen throughout the body. This study aims to analyze determinants related to the incidence of anemia in postpartum mothers in the working area of ​​the Darussalam Health Center, Aceh Besar Regency in 2024.This research was conducted in July 2024.This research is analytical using the cross sectional method. The sampling technique was carried out using a total sampling of 35 people. Data were collected through Hb level checks using GCHb easy touch and interviews with questionnaires. Univariate data were analyzed descriptively and bivariate data were analyzed using the chi square test. There was a significant relationship between age and the incidence of anemia in postpartum mothers using the Pearson chi-square test with a value of p = 0.000 (p<0.05). There was a significant relationship between the type of delivery and the incidence of anemia in postpartum mothers using the Pearson chi-square test with a value of p = 0.001 (p<0.05). There was a significant relationship between the consumption of Fe tablets and the incidence of anemia in postpartum mothers using the pearson chi-square test with a value of p = 0.000 (p<0.05).